The influence of organizational factors on work engagement among academics at Malaysian research universities - Tauhed, Siti Zainab; Mohd Rasdi, Roziah; Abu Samah, Bahaman; Ibrahim, Rahinah (Human Resource Management Academic Research Society, 2018)
The purpose of this paper is to examine the influence of organizational factors, i.e. organizational culture, transformational leadership and professional development on academics work engagement (WE) at Malaysian Research Universities (MRUs). The descriptive survey design was employed in this study and a questionnaire was used to collect data from the respondents. This study employed the proportionate stratified random sampling to select 381 sample of academics at MRUs. The data of this study were analyzed using the descriptive statistics and multiple regression. The results show that organizational culture, transformational leadership, and professional development significantly influence the work engagement of academics. This study is important for the Human Resource Development practitioners and university’s management to identify factors and plan strategies of interventions to enhance academics engagement in their job. This paper contributes to a perceived gap in past studies that have little attention in investigating the influence of organizational factors on work engagement.